Censorship as an Instrument to Protect the Public Interest: The Conceptual Framework - Asma Md. Isa; Wan Amizah Wan Mahmud; Wan Idros Wan Sulaiman; Muhammad Adnan Pitchan; Haslina Mohamed Hassan; Umi Hamidaton Mohd Soffian Lee (PalArch's Journals, 2024)
Non-Indexed Publication